2011
DOI: 10.1007/s00270-011-0146-6
|View full text |Cite
|
Sign up to set email alerts
|

Intraluminal Radioactive Stent Compared with Covered Stent Alone for the Treatment of Malignant Esophageal Stricture

Abstract: Intraluminal radioactive stent loaded with iodine-125 seeds implantation was a feasible and practical management in treating malignant esophageal stricture and was superior to covered stent alone insertion, as measured by survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 26 publications
1
26
1
1
Order By: Relevance
“…Certain studies have shown that a self-expandable stent loaded with 125 I seeds is a safe and effective treatment for esophageal cancer (9,10). However, the 125 I seeds must be installed in the esophageal stent every time the procedure is performed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Certain studies have shown that a self-expandable stent loaded with 125 I seeds is a safe and effective treatment for esophageal cancer (9,10). However, the 125 I seeds must be installed in the esophageal stent every time the procedure is performed.…”
Section: Discussionmentioning
confidence: 99%
“…The half-life of the 125 I seeds was 59.6 days. The radiation dose was determined on the basis of the size of the individual tumor, according to clinical studies, and the activity for clinical use was 5–13.5 mCi (910). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of them suggested that radioactive stent were relatively safe and easy to apply. Some of them claimed longer stent patency period and survival period than conventional metal stents with statistically significant difference, although clinical application is still quite early considering their small sample sizes 36-38…”
Section: Studies For Functional Stentmentioning
confidence: 99%
“…Metal stents became more and more popular for patients who encountered dysphagia [ 9 , 10 ]. Recently, an esophageal stent embedded with iodine-125 ( 125 I) seeds (also called intraluminal radiotherapy) has been developed [ 11 , 12 ]. These two kinds of stents are more and more useful for inoperable esophageal cancer [ 13 17 ].…”
Section: Introductionmentioning
confidence: 99%